Oral lymphangioma of the buccal mucosa a rare case report - Saligrama Seema Yoganna; Rame Gowda Gowda Rajendra Prasad; B Sekar (Wolters Kluwer Medknow Publications, 2014)
The lymphangioma are benign hamartomatous tumors of lymphatic vessels that arises from the sequestration of lymphatic that fails to communicate with the lymphatic system. Most common intra oral site being the anterior two-thirds of tongue, usually superficial in location and demonstrates a pebbly surface that resembles a cluster of translucent vesicles, they are typically soft and fluctuant masses. Secondary hemorrhage into the lymphatic spaces may cause some of these vesicles to become purple. They have been known to grow to large size causing difficulties in mastication and speech. A variant of lymphangioma is cystic hygroma grows as lymphatic anomaly found in the neck commonly present with significant airway obstruction. We present a rare case of lymphangioma affecting the buccal mucosa of a 14-year-old male.